Interpersonal Shame, Self-Concealment, and Suicidality for Asian American Adults - Hogge, Ingrid; Straughan, Anna; Kranendonk, Jacob; Kim, Eunha (International Journal for the Advancement of Counselling, 2025)
This study explored culturally salient predictors of suicide risk for Asian Americans. We examined the relationship between two forms of interpersonal shame (external and family) and suicidality. External interpersonal shame arises from concerns of being negatively evaluated by others whereas family-focused shame stems from perceptions that one has brought shame to one’s family. Self-concealment, which is a pattern of withholding personal information from others, was also included as a moderator to better understand the conditions in which interpersonal shame might be more or less deleterious. A sample of Asian American adults (n = 182) completed an online survey. Participants were mostly female/women (79.7%), and the average age was 34.19 years (SD = 12.43). Our results revealed both external- and family-related interpersonal shame were associated with increased suicidality, even after controlling for negative affect. Self-concealment significantly moderated the relationship between family-related, but not external, interpersonal shame. Family-related shame was associated with greater suicidality at the low and medium levels of self-concealment. However, this effect was non-significant at the highest level of self-concealment. Contrary to previous research, high self-concealment did not exacerbate the effect of family-related interpersonal shame on suicidality. We discuss implications for suicide research, intervention, and prevention for Asian Americans.
Keywords: Asian American psychology; Interpersonal shame; Self-concealment; Suicide